Therapeutic effect of gradual attention training on language function in patients with post-stroke aphasia: a pilot study. (November 2019) - Zhang, Hong; Li, He; Li, Ruojin; Xu, Guoxing; Li, Zhenlan
Objective: To investigate the effect of gradual attention training on language function with aphasia. Design: Randomized controlled trial. Participants: A total of 40 patients (mean age: 53.47 years) with post-stroke aphasia came from the stroke rehabilitation unit of rehabilitation department in the First Hospital of Jilin University, of which 13 (32.5%) had intracerebral hemorrhage, 28 inpatients and 12 outpatients, 11 women and 29 men, 34 within three-month stroke and 6 within three months to one year. Interventions: All participants were divided into control and experimental groups. Both groups received language treatment 20 minutes a day, six days/week, for five weeks, and the experimental group received gradual attention training 20 minutes a day, six days/week, for five weeks. Main measures: Language function was assessed pre- and post-treatment by components of the Western Aphasia Battery (WAB) which included spontaneous speech, auditory comprehension, repetition, and naming and then calculated the aphasia quotient (AQ). Results: The mean (SD) AQ of the experimental group and control group, respectively, was 25.71 (12.63) and 26.2 (12.31) at baseline. After treatment, the AQ mean (SD) was 43.08 (15.14) in the experimental group, which showed a significant improvement compared to 33.48 (14.04) in the control group ( P = 0.02).All items of WAB were higher in experimental group than those in control group, especially in auditory comprehension and naming ( P = 0.02, 0.01). Conclusion: Gradual attention training seemed to improve language function in post-stroke aphasia, specifically function of listening comprehension and naming.